2022
DOI: 10.3390/antibiotics11030331
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay among Radiation Therapy, Antibiotics and the Microbiota: Impact on Cancer Treatment Outcomes

Abstract: Radiation therapy has been used for more than a century, either alone or in combination with other therapeutic modalities, to treat most types of cancer. On average, radiation therapy is included in the treatment plans for over 50% of all cancer patients, and it is estimated to contribute to about 40% of curative protocols, a success rate that may reach 90%, or higher, for certain tumor types, particularly on patients diagnosed at early disease stages. A growing body of research provides solid support for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 122 publications
(195 reference statements)
0
11
0
Order By: Relevance
“…So far, some preclinical and few small clinical studies have suggested that the gut microbiome can modulate the anti-tumor and normal tissue effects of radiotherapy [ 16 , 27 30 ]. For instance, Crawford and Gordon could detect a radioprotective role of fasting-induced adipose factor, whose expression is suppressed by gut microbiota, on the intestinal epithelium [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, some preclinical and few small clinical studies have suggested that the gut microbiome can modulate the anti-tumor and normal tissue effects of radiotherapy [ 16 , 27 30 ]. For instance, Crawford and Gordon could detect a radioprotective role of fasting-induced adipose factor, whose expression is suppressed by gut microbiota, on the intestinal epithelium [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the risk for severe infection-related complications, for which HNSCC patients often exhibit risk factors such as lymphopenia and malnutrition, must be critically weighted against the potential negative microbiome alterations caused by antibiotics [ 35 ]. In the future, (tailored) administration of probiotics or fecal microbiome transfers may be other approaches to address antibiotics-induced microbiome alterations; however, so far, these approaches are mainly examined with the aim to alleviate radiotherapy-induced normal tissue toxicities but not to increase the anti-tumor efficacy of radiotherapy (reviewed in [ 21 ] and [ 30 ]). At least for immune checkpoint inhibitor treatment, there are preclinical and early clinical studies showing the potential of those approaches to increase the anti-tumor immune response [ 13 , 36 , 37 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A bidirectional relationship between RT and the gut microbiota exists. 341 One of the adverse events of radiotherapy is gut microbiota dysbiosis, which is typically characterized by a relative decrease in the richness of favorable microbes, e.g., Bifidobacterium , and an increase in the relative richness of harmful microorganisms such as Fusobacteria and Proteobacteria , 342 and these changes in the composition of gut microbiota in turn exacerbates radiation-related complications, such as radiation enteropathy. 343 , 344 However, the presence of some commensal microbes is critical for improving the efficacy of radiotherapy and moderating RT-related adverse events.…”
Section: Cancer-related Microorganisms and Effectorsmentioning
confidence: 99%
“…Second, radiation exposure can cause the formation of ROS, which are chemically active due to their unpaired electrons and can damage the DNA and other cellular structures of the intestinal microbiota, thereby triggering changes in the bacterial flora ( 81 ). In addition, the various microorganisms that make up the intestinal microbiota have different intrinsic radio-sensitivities ( 82 ), so radiation exposure can alter the composition and relative proportions of the microbiota.…”
Section: Microbiota and Crc Radiotherapymentioning
confidence: 99%